Jawabanmu

2014-04-05T22:08:00+07:00
    f (x) = mx + n
   f (-1) = -1m + n = 2
   f (2) =  2m  + n = 11 _
                -3m   = -9
                    m   = 3
 
2 . m + n = 11 
2 . 3 + n  = 11
     6 + n  = 11
           n = 5

f (4) = 4 . m + n
      = 4 . 3 + 5
      = 12 + 5
      = 17 
1 2 1
2014-04-05T22:28:39+07:00
F(-1)=2              f(x)=mx+n              f(4)=mx+n
f(2)=11-            f(2)=11                         3.4+5
= -3m=-9           f(x)=3.2+n                   17  jadi jawabnaya 17
m=-9                  11=6+n 
    -3=3             11-6=n
                          5=n